2021
DOI: 10.1055/a-1524-5155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Electronic Cigarette Exposure On Foetal Development: a Review of the Literature

Abstract: Since their market launch in 2007, e-cigarettes gained popularity and were considered a relatively safe alternative to traditional cigarettes. Pregnant women and women of childbearing age in particular are increasingly turning to e-cigarettes. Little is known about the effects of prenatal exposure on the affected foetus. This paper aims to provide an overview of the current research on the effects of prenatal e-cigarette exposure on the foetus. Since studies in humans are lacking to date, this review refers on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
(291 reference statements)
0
1
0
Order By: Relevance
“…Four reviews reported conflicting results on the effects of ENDS use on pregnancy outcomes 95–98. Romer et al indicated that exposure to nicotine in ENDS could cause low birth weight, miscarriage and stillbirth 96. Calder et al indicated that ENDS use has less effect on birth weight outcomes than CC smoking 95.…”
Section: Resultsmentioning
confidence: 99%
“…Four reviews reported conflicting results on the effects of ENDS use on pregnancy outcomes 95–98. Romer et al indicated that exposure to nicotine in ENDS could cause low birth weight, miscarriage and stillbirth 96. Calder et al indicated that ENDS use has less effect on birth weight outcomes than CC smoking 95.…”
Section: Resultsmentioning
confidence: 99%